PERAN BUMDES SIMPAN PINJAM UNTUK PEMBERDAYAAN EKONOMI MASYARAKAT DI DESA WAYABULA TINJAUAN EKONOMI ISLAM - Quilim, Cici Aryansi; Juleng, Julmiati (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2021)
The purpose of this study was to determine the role of Savings and Loans Village Owned Enterprises (BUMDes) on community economic empowerment and an overview of Islamic economics on the economic empowerment of the Wayabula Village community. The analysis used is descriptive qualitative, with primary and secondary data obtained by means of field observations, interviews and documentation. The results of the study reveal that the BUMDES Savings and Loans is still standing today and in an effort to empower the people of Wayabula Village, BUMDES provides assistance in the form of loans and business capital to small communities and helps improve the economic welfare of the community. Based on an Islamic economic review, the form of BUMDES savings and loans does not meet the rules of Islamic law because it still uses the interest system.